The prevalence of undiagnosed pre-surgical cognitive impairment and its post-surgical clinical impact in elderly patients undergoing surgery for adult spinal deformity - Adogwa, Owoicho; Elsamadicy, Aladine A.; Lydon, Emily; Vuong, Victoria D.; Cheng, Joseph; Karikari, Isaac O.; Bagley, Carlos A. (Journal of Spine Surgery; Vol 3, No 3 (September 29, 2017): Journal of Spine Surgery, 2017)
Background: Pre-existing cognitive impairment (CI) is emerging as a predictor of poor post-operative outcomes in elderly patients. Little is known about impaired preoperative cognition and outcomes after elective spine surgery in this patient population. The purpose of this study was to assess the prevalence of neuro CI in elderly patients undergoing deformity surgery and its impact on postoperative outcomes. Methods: Elderly subjects undergoing elective spinal surgery for correction of adult degenerative scoliosis were enrolled in this study. Pre-operative baseline cognition was assessed using the Saint Louis Mental Status (SLUMS) test. SLUMS consists of 11 questions, which can give a maximum of 30 points. Mild CI was defined as a SLUMS score between 21–26 points, while severe CI was defined as a SLUMS score of ≤20 points. Normal cognition was defined as a SLUMS score of ≥27 points. Complication rates, duration of hospital stay, and 30-day readmission rates were compared between patients with and without baseline CI. Results: Eighty-two subjects were included in this study, with mean age of 73.26±6.08 years. Fifty-seven patients (70%) had impaired cognition at baseline. The impaired cognition group had the following outcomes: increased incidence of one or more postoperative complications (39% vs. 20%), higher incidence of delirium (20% vs. 8%), and higher rate of discharge institutionalization at skilled nursing or acute rehab facilities (54% vs. 30%). The length of hospital stay and 30-day hospital readmission rates were similar between both cohorts (5.33 vs. 5.48 days and 12.28% vs. 12%, respectively). Conclusions: CI is highly prevalent in elderly patients undergoing surgery for adult degenerative scoliosis. Impaired cognition before surgery was associated with higher rates of post-operative delirium, complications, and discharge institutionalization. CI assessments should be considered in the pre-operative evaluations of elderly patients prior to surgery.